Poetry in the Academy: A Language of Possibility - Leggo, Carl (Canadian Journal of Education/Revue canadienne de l’éducation, 2018)
As a poet, researcher, and teacher in the academy, I have pursued my vocation with an abiding commitment to both creative and critical discourse. I inquire into my autobiographical experiences as a poet, researcher, and teacher in the institutional contexts of a Faculty of Education by creating a performance of poetry that seeks to honour imagination, heart, and intellect. My goal is to offer a hopeful testimony to the value of giving curricular and pedagogical attention to the significance of critical creativity in education. In the performance I weave poetry, personal recollections, reflections, and quotations from writers who have inspired me. In this article, I present a performative text that is both poetic and full of poetry. I invite readers to receive this article like a long poem, full of resonances and gaps, fragments and sparks. I engage in testimony, in witness, in presenting prose and poetry that are enthused with an educator’s delight in the creative playfulness of words.